ANALISIS KESESUAIAN LAHAN UNTUK TANAMAN KULIT MANIS (CINNAMOMUN BURMANII) DI KECAMATAN SUNGAI TARAB KABUPATEN TANAH DATAR - desonia, ega resta (JURNAL BUANA, 2026)
This research aims to determine: 1) Land characteristics of Sungai Tarab District in terms of soil conditions, topography and climate; 2) Level of land suitability for sweet skin crops in Sungai Tarab District; 3) Falling prices due to instability in sweet skin production in Sungai Tarab District. This research is a quantitative descriptive study that describes the situation in the field. This research uses the maching method with a limiting factor approach to analyze the suitability of cinnamon land. Based on the results of the research, it was found: 1) The physical characteristics of the land in Sungai Tarab District are classified as suitable, but based on drainage and base saturation, a few areas have limited drainage and moderate steel saturation or >35; 2) The level of suitability of cinnamon land in Sungai Tarab District based on limiting factors has various suitability classes consisting of 2 classes, namely suitable (S2) with an area of ​​4372.88 Ha and marginally suitable (S3) with an area of ​​3960.66 Ha; 3) Decreasing productivity and falling prices caused by several limiting factors such as the quality of cinnamon and high rainfall will affect the quality of cinnamon itself. Keywords: Sweet Skin, Maching, Land Characteristics, Land Suitability